Obstructive Sleep Apnoea Syndrome In Morbidly Obese Children With Slipped Capital Femoral Epiphysis (Scfe) - NEELKANT.S,; SAMEENA,; SREEKANTHA, (International Journal of Pharma and Bio Sciences, 2012)
There is a increase in incidence of obesity in recent days and obesity is one of the etiological factor for SCFE and Sleep apnoea syndrome.During this study period we have taken 15 patients with SCFE, in that, 11patients were morbidly obese and 9 patients had sleep apnoea documented by polysomnography.We found that incidence of Sleep apnoea in patients requiring surgery for SCFE is 60%.Mean REM total sleep time 18%,oxygen saturation 82.8%,arousal index per hour 16.5.All 9 patients were treated preoperatively for sleep apnoea syndrome,so there were no complications during surgery for SCFE.